Characterization of Nonlinear Integrated Capacitors - Sutory, Tomas; Kolka, Zdenek (Společnost pro radioelektronické inženýrství, 2008)
The paper deals with a modified CBCM (Charge-Based Capacitance Measurements) method for nonlinear capacitance characterization. The method is characterized by high resolution although it is based on equipment found in any average laboratory. CBCM was originally developed for linear interconnect measurements. The proposed modification uses two DC swept sources to measure the whole nonlinear Q-v characteristic in both polarities without the necessity to switch the measured object. A test-chip implementing the method was designed and manufactured in the 0.35μm CMOS process. Verifica- tion against known capacitances proved the correctness and accuracy of the method. It was successfully used for MOSCAPs characterization.
Keywords: Charge-based capacitance measurements; structures; MOS capacitors; integrated circuits. Test